Pseudoaneurysm of the femoral artery after cardiac catheterisation: diagnosis and treatment by manual compression guided by Doppler colour flow imaging. Issue 1 (July 1994) - Currie, P; Turnbull, C M; Shaw, T R
Abstract : OBJECTIVE--To assess the value of Doppler colour flow imaging for diagnosing and guiding non-surgical treatment of pseudoaneurysm of the femoral artery complicating cardiac catheterisation. DESIGN--A prospective study. SETTING--Cardiac department in a teaching hospital. PATIENTS--9 patients (8 female, 1 male) who presented with pseudoaneurysm 1-15 days after cardiac catheterisation. INTERVENTIONS--The femoral arterial communication to the false aneurysm was localised by Doppler colour flow imaging. Manual pressure was then applied to the ultrasound transducer which was positioned directly over the site of the arterial communication. Pressure was progressively increased until it was sufficient to prevent colour flow from the artery into the false aneurysm cavity while allowing Doppler flow to continue within the arterial lumen. MAIN OUTCOME MEASURES--Characteristics of pseudoaneurysm, duration of manual compression, success rate, follow up. RESULTS--The pseudoaneurysms ranged from 1.3 to 5.5 cm in length. Six pseudoaneurysms were 1.3-2.0 cm away from the arterial puncture. The pseudoaneurysm was closed in 8/9 patients by compression exerted manually through the transducer for 25-40 minutes (3 successful cases required two or three periods of compression within 48 hours). No pseudoaneurysm recurred during 14-61 days of follow up. CONCLUSIONS--Most pseudoaneurysms of the femoral artery can be treated by a period of manual pressure applied with an ultrasound transducer and guided by Doppler colour flow.